The Court of Public Procurement in Chile: A critical analysis and some proposals - Escanilla Abarza, Eduardo S. (Derecho Público Iberoamericano, 2013)
This article proposes to analyze the experience of the Chileans Court of Public Contracts, scrutinizing it under an approach related a traditional juridical view and with functional approaches. The purpose is to offer issues for a legislative agenda debate oriented to optimize its performance.